Robust Minimmun Variance Beamformer using Phase Aberration Correction Methods - Chau Loo Kung, Gustavo Ramón (2017)
The minimum variance (MV) beamformer is an adaptive beamforming method that has the potential to enhance the resolution and contrast of ultrasound images. Although the sensitivity of the MV beamformer to steering vector errors and array calibration errors is well-documented in other fields, in ultrasound it has been tested only under gross sound speed errors. Several robust MV beamformers have been proposed, but have mainly reported robustness only in the presence of sound speed mismatches. Additionally the impact of PAC methods in mitigating the effects of phase aberration in MV beamformed images has not been observed Accordingly, this thesis report consists on two parts. On the first part, a more complete analysis of the effects of different types of aberrators on conventional MV beamforming and on a robust MV beamformer from the literature (Eigenspace-based Minimum Variance (ESMV) beamformer) is carried out, and the effects of three PAC algorithms and their impact on the performance of the MV beamformer are analyzed (MV-PC). The comparison is carried out on Field II simulations and phantom experiments with electronic aberration and tissue aberrators. We conclude that the sensitivity to speed of sound errors and aberration limit the use of the MV beamformer in clinical applications, and that the effect of aberration is stronger than previously reported in the literature. Additionally it is shown that under moderate and strong aberrating conditions, MV-PC is a preferable option to ESMV. On the second part, we propose a new, locally-adaptive, phase aberration correction method (LAPAC) able to improve both DAS and MV beamformers that integrates aberration correction for each point in the image domain into the formulation of the MV beamformer. The new method is tested using fullwave simulations of models of human abdominal wall, experiments with tissue aberrators, and in vivo carotid images. The LAPAC method is compared with conventional phase aberration correction with delay-and-sum beamforming (DAS-PC) and MV-PC. The proposed method showed between 1-4 dB higher contrast than DAS-PC and MV-PC in all cases, and LAPAC-MV showed better performance than LAPAC-DAS. We conclude that LAPAC may be a viable option to enhance ultrasound image quality of both DAS and MV in the presence of clinically-relevant aberrating conditions.